FORM GIVING DESIGN EXPLORATION INSPIRED BY The 1980s MEMPHIS DESIGN WITH MORPHOLOGICAL CHART ANALYSIS - Devanny Gumulya; Hendrawan Sutikno; Rudy Pramono; Evo Sampetua Hariandja (Universitas Trisakti, 2021)
AbstractThe paper studies how morphological chart that comes from engineering method be applied in a creative design process that promotes both divergent and logical thinking. Morphological chart offers vast of possibility of design exploration that can be very useful for educating nascent designers. On the other hand, history has inspired many designers to create many new things. Memphis is postmodernism design style happened between 1981-1987 that was characterize by form follow fun paradigm by creating objects that are bizarre from common object during the time. The paper presents the findings by reviewing four morphological charts, generating 20 new ideas ranging from very similar to less similar style with Memphis. The reviews discovered three key factors affecting design divergence using the morphological chart method: level of variation, which deals how many variations the means can provide, the more variations the more novelty ideas be yielded. Level of unity means show how each element taken from the means be in harmony with each other. Level of abstraction means that the degree how far the idea from the origin inspiration. By having the three level, ideas generated from morphological chart can yield better design.Abstrak Paper ini mempelajari bagaimana chart morfologi yang berasal dari ilmuteknik diterapkan dalam proses desain kreatif yang memungkinkan pemikiran divergen dan logis digunakan bersama-sama. Chart morfologi menawarkan banyak kemungkinan eksplorasi desain yang bisa sangat berguna untuk mendidik mahasiswa desain. Di sisi lain, sejarah telah menginspirasi banyak desainer untuk menciptakan banyak hal baru. Memphis adalah gaya desain postmodernisme yang terjadi antara 1981-1987 yang dicirikan dengan bentuk mengikuti paradigma “form follow fun” dengan menciptakan objek yang aneh dari objek umum di era 1980an. Paper ini menyajikan temuan dengan meninjau empat chart morfologi yang menghasilkan 20 ide baru mulai dari yang sangatmirip dengan gaya Memphis hingga yang berbeda dengan Memphis. Hasilstudi menemukan tiga faktor utama yang mempengaruhi divergensi desain menggunakan metode chart morfologi: tingkat variasi, seberapa banyak variasi elemen ide maka ide yang dihasilkan akan semakin baru. Tingkat kesatuan berarti menunjukkan bagaimana setiap elemen yang diambil selaras satu sama lain. Tingkat abstraksi berarti seberapa jauh ide dari inspirasi asal. Dengan memiliki tiga tingkat ini, ide yang dihasilkan dari chart morfologi akan semakin membaik.